1949
DOI: 10.1097/00006842-194911000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Psychologic Correlations with the Electroencephalogram

Abstract: and the late P. A. DAVIS, M.D.I N 1937 we published a brief note (10) describing two major correlations between the electroencephalogram (EEG) and the psychologic organization of the individual. The psychologic formulations were based on psychoanalytic data and other information available on 66 patients at the Institute for Psychoanalysis in Chicago. From 1937 through 1940 we obtained annually additional EEG records (with improved technic) on as many as possible of the original group and also on nearly one hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
1

Year Published

1955
1955
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 4 publications
1
3
0
1
Order By: Relevance
“…This finding is contrary to that of Henry and Knott (11) who found no alpha differences between introverted and extraverted subjects. However, Saul, Davis and Davis (20), and Davis and Davis (3), have pointed out relations between passive personality trends and high alpha indices which would tend to support the present findings. Our method of determining introversion (M/Sum C) is akin to the psychoanalytic approach used by these latter authors, and quite different from the appraisal method used by Henry and Knott (Nebraska personality inventory).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…This finding is contrary to that of Henry and Knott (11) who found no alpha differences between introverted and extraverted subjects. However, Saul, Davis and Davis (20), and Davis and Davis (3), have pointed out relations between passive personality trends and high alpha indices which would tend to support the present findings. Our method of determining introversion (M/Sum C) is akin to the psychoanalytic approach used by these latter authors, and quite different from the appraisal method used by Henry and Knott (Nebraska personality inventory).…”
supporting
confidence: 76%
“…Several studies have related theta activity with aggressive psychopathic personalities (8,10,15). Others (19,20) have reported that passive and receptive personality trends are most striking in people with the greatest alpha activity. It is interesting that at least one study (16) associates the theta pattern with shy, immature, schizoid types of personality that, at times, show symptoms of aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Saul et al (162,163) proposed several relationships between normal EEG patterns and certain personality characteristics: (a) Passive individuals tend to have regular, persistent alpha rhythms of high index, and "masculine competitive" individuals tend to have low voltage, weak alpha rhythms of low index. They defined passivity as connoting "dependence, submissiveness, the desire to receive from others, and readiness to retreat from dangers, effort, and responsibility.…”
Section: Personalitymentioning
confidence: 99%
“…Sin embargo, consideramos necesario este estudio teniendo en cuenta que el EEG es un medio de exploración funcional del sistema nervioso que manifiesta la interacción de los distintos niveles (Hill 13, Lairy y Dell 18). Y en las condiciones de nuestro trabajo, aun cuando no eran de esperar grandes alteraciones, habría de producirse sin duda un cierto grado de perturbación funcional, que debería manifestarse en alguna modificación de la constancia morfológica individua] del EEG (Saul, Davis y Da vis 22).…”
unclassified